2007
DOI: 10.1080/10915810701369709
|View full text |Cite
|
Sign up to set email alerts
|

Safety Studies Regarding a Standardized Extract of Fermented Wheat Germ

Abstract: "Avemar pulvis" is a powder consisting of an aqueous extract of fermented wheat germ, with the drying aids maltodextrin and silicon dioxide, standardized to contain approximately 200 microg/g of the natural constituent 2,6-dimethoxy-p-benzoquinone. The results of toxicological and clinical studies of this product demonstrate its safety for its intended use as a dietary supplement ingredient in the United States. Avemar pulvis has been used in Hungary since 1998 and is approved in that country, as well as in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 11 publications
0
27
0
Order By: Relevance
“…However, the percentage of apoptotic cells reached a maximum of 48% at a concentration of 300 μg/ml since higher dosage of the drug (600 μg/ml) was not able to significantly intensify the observed effect. This might be the reason for the fact that Avemar demonstrated no signs of toxicity in various studies (25), whereas more potent anticancer drugs exert a number of dose-limiting toxic side effects when applied to humans.…”
Section: Discussionmentioning
confidence: 99%
“…However, the percentage of apoptotic cells reached a maximum of 48% at a concentration of 300 μg/ml since higher dosage of the drug (600 μg/ml) was not able to significantly intensify the observed effect. This might be the reason for the fact that Avemar demonstrated no signs of toxicity in various studies (25), whereas more potent anticancer drugs exert a number of dose-limiting toxic side effects when applied to humans.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of Avemar are manifold (3)(4)(5)(6)(7). On the contrary, it shows no toxicity, mutagenicity, or genotoxicity (8). Moreover, the combination of Avemar with chemotherapeutic agents did not increase the toxicity or reduce antiproliferative activity (9).…”
Section: Avemar-a Special Nutriment For Cancer Patientsmentioning
confidence: 97%
“…Its subacute toxicity is also very low, as no toxicity was observed at the highest dose tested in rats, 1868 mg/kg. 17) Kim et al 11) tried to assess the anti-obesity effect of yeast hydrolysate with below 10 kDa molecular weight and found that it reduced body weight in SD rats fed a high fat diet. To investigate the effects of yeast hydrolysate with below 10 kDa molecular weight on appetite regulation mechanisms in Values are means ± S.D.…”
Section: Discussionmentioning
confidence: 99%